Pemodelan Matematika dalam Kajian Sistem Antrian pada Counter Kasir Mixue di Jalan Pahlawan Kota Magelang - Azziizah Dinda Ammara; Sarnefa Mulya Prastiwi; Rizky Catur Prayogi; Yesi Franita (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2025)
This study uses the Mean Value Analysis (MVA) approach to analyze the queuing system at the Mixue Ice Cream & Tea cashier counter on Jalan Pahlawan in Magelang City. The MVA method was chosen because it can handle general time distributions between arrivals and services. The research was conducted through direct observation and interviews over the course of two days, during which time data was collected on the time between arrivals and customer service. The analysis revealed that the system was not in a steady state, as the arrival rate (0.0122 customers per second) exceeded the service rate (0.0111 customers per second). High service variability (CV = 276.30%) compared to arrival variability (CV = 69.46%) indicates service instability. On average, customers waited 47.08 seconds, and the total time in the system was 137.17 seconds. These results are important because they indicate the need for increased efficiency and standardized services to prevent a decrease in service quality.